Penerapan Sistem Informasi Inventori Gudang Kayu untuk Alat Kontrol Persediaan Studi Kasus: PT. Bina Megah Indowood - Elisa Kevin Giovanni; Alexander Setiawan; I Gede Agus Widyadana (Universitas Kristen Petra, 2022)
PT Bina Megah Indowood (BMI) is a company that provides high quality solid wood floors, with a choice of thicknesses to meet various needs. PT. BMI itself has several warehouse divisions with different functions. However, with such a large warehouse area, the obstacles often experienced by companies are still minimal use of information technology, such as for example manual data processing, and errors in recording, and as a result the recording process by PPIC is disrupted and the company's business processes are a little late.With this background, it will be done to find a solution by designing an inventory information system at PT. Bina Megah Indowood. With the application of information technology, it is hoped that PT Bina Megah Indowood can correct errors that often occur in the field, shorten existing data processing, so as to improve labor efficiency and minimize data input errors that occur in the field.The test results on the manufacture of the Inventory Control and Monitoring system at PT. Bina Megah Indowood show that the system can perform data calculations correctly. So that the data obtained can meet precise and controlled calculations and can reduce errors that occur in the field. Testing for reports from inventory control is also successful, as evidenced by the resulting reports that can calculate all the stock owned by each warehouse properly and accurately. This is useful so that the company will no longer have trouble seeing and monitoring the stock they have.